Kontramitos Keluarga Ideal dalam Novel Kita Pergi Hari Ini Karya Ziggy Zesyazeoviennazabrizkie - Adzkia Sabila; Aldi Aditya; Ummi Nurjamil Baiti Lapiana (Universitas Sebelas Maret, 2024)
The concept of the ideal family in Indonesian society has been embedded since the 20th century, especially during the new order era. However, in the novel we go today, there is a cat figure who acts as the main monster in the novel. This novel provides in illustration that monster figures can appear from those closest to them, namely family members. This research uses descriptive analysis methods, with content analysis techniques. The theory used is the myth put forward by Roland Barthes.